Pengembangan dan Penerapan EFDE Gen 3 dengan Pemanfaatan Visualcam Untuk Identifikasi Dampak Mitigasi Lapangan Secara Real-time - Nila, Ida Ratna; Alamsyah, Wan (E-Jurnal Universitas Samudra, 2022)
Wireless-based technology development, particularly the Internet of Things system, is currently in high demand in a variety of industries, including disaster mitigation. A catastrophe mitigation system will be built as an Internet of Things-based weather station that leverages solar system technology as a power source in this research. Because this utility is a development of the previous version, EFDe, it is known as EFDe Gen 3. This EFDe Gen 3 tool's monitoring mechanism is built on a visual cam that can reach full target range access. Using an ultrasonic sensor, the operating system of this tool is designed to detect changes in water level as early as possible and issue a disaster alarm at the appropriate time in real-time at a dam or sluice (HC-SR04). This instrument also has a measuring limit as well as an IP camera mounted on the solar panel pole. When the water level hits 40 cm, the Arduino Uno will turn on and send an alarm with a link to the flood's location, after which the camera will capture a picture. The URL can be accessed, and the location of the flood can then be determined. It is envisaged that with this instrument, Langsa City, in general, and Samudra University, in particular, will be able to establish their weather station to monitor weather developments and serve as a disaster mitigation system for lessening the consequences of natural disasters.